2006
DOI: 10.1111/j.1365-2133.2006.07205.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant correlation between the CD63 assay and the histamine release assay in chronic urticaria

Abstract: The CD63 expression assay seems to be a reliable functional test in the diagnosis of ACU, particularly if highly sensitive donor basophils are used, but the determination of the sCD40L serum level was not sufficient to differentiate between the autoimmune and the nonautoimmune patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 35 publications
3
56
1
3
Order By: Relevance
“…Our study is one of the first to compare CD63 and CD203c expression in a group of CU patients. Based on experience of other authors, who demonstrated that atopic donor basophils showed marked upregulation of CD63 and CD203c molecules after stimulation with serum from CU patients in this study we used highly atopic donor basophils [12,14,15]. Our study confirmed that serum from patients with CU, but not control sera, on average significantly upregulated atopic donor basophil CD63 and CD203c expression.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our study is one of the first to compare CD63 and CD203c expression in a group of CU patients. Based on experience of other authors, who demonstrated that atopic donor basophils showed marked upregulation of CD63 and CD203c molecules after stimulation with serum from CU patients in this study we used highly atopic donor basophils [12,14,15]. Our study confirmed that serum from patients with CU, but not control sera, on average significantly upregulated atopic donor basophil CD63 and CD203c expression.…”
Section: Discussionsupporting
confidence: 81%
“…After ROC curve analysis, we concluded that CD203c did not have sufficient diagnostic power. Other authors, who tested CD63 [11][12][13][14][15] or CD203c expression [17] in CU patients, found significant correlation between ASST and both basophil activation tests positivity. The discrepancy between CD63 and CD203c correlations with ASST in our study can reflect either different mechanism of CD63 and CD203c molecules upregulation or differences in methodology of tests.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One of them, the gold standard, is the basophil histamine release (HR) test [18]. In recent studies, a new method, the modified CD63 expression assay, was found to be a reliable method for the diagnosis of AIU [19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…The basophil histamine release assay (HRA) is currently the "gold standard" for detecting functional antibodies in the serum of patients with CU [5][6][7]. Improved screening tests have been sought in the last decade; for instance, flow cytometry used to determine the ability of a CU patient's serum to evoke an expression of CD63 and CD203c on donor basophils is showing some promise [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%